Opportunity and preference learning - Christian Schubert (Max Planck Institute of Economics, 2012)
Robert Sugden has recently elaborated upon the case for a normative standard of freedom as opportunity that is supposed to cope with the problem of how to realign normative economics - with its traditional rational choice orientation - with behavioral economics. His standard, though, presupposes that people respond to uncertainty about their own future preferences by dismissing any kind of self-commitment. We argue that the approach lacks psychological substance: Sugden's normative benchmark - the responsible person - is a purely artificial construct that can hardly serve as a convincing role model in a contractarian setting. An alternative concept is introduced, and some policy implications are briefly discussed.
Keywords: D51; D63; 330; Opportunity Criterion; Preference Change; Reconciliation Problem; Verhaltensökonomik; Präferenztheorie; Persönlichkeitspsychologie; Theorie